2023
DOI: 10.3389/fendo.2023.1202686
|View full text |Cite
|
Sign up to set email alerts
|

Weight bearing training alleviates muscle atrophy and pyroptosis of middle-aged rats

Pengyu Fu,
Lijing Gong,
Luyao Yang
et al.

Abstract: BackgroundAge-related muscle atrophy and adipose accumulation begin to occur in young and middle-aged individuals, and exercise at an early age improves body composition. Pyroptosis may play an essential role in age-related low-grade inflammation. This study aimed to explore the alleviation of muscle atrophy by weight-bearing training with increasing age via inhibition of pyroptosis.MethodsNinety 8-month-old male SD rats were randomly divided into three groups: (1) normal baseline group (N group, n = 10), sacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The effect of exercise on treating chronic conditions is of significant physiologic and clinical importance ( 105 ). Our previous study has shown that weight-bearing running training alleviates age-related muscle atrophy by inhibiting the expression of pyroptosis-related genes in adipose tissue ( 106 ). Understanding the role of pyroptosis in chronic diseases such as DM allows for prevention and personalized treatment strategies.…”
Section: Exercise On Improving Diabetic Complications By Targeting Py...mentioning
confidence: 99%
“…The effect of exercise on treating chronic conditions is of significant physiologic and clinical importance ( 105 ). Our previous study has shown that weight-bearing running training alleviates age-related muscle atrophy by inhibiting the expression of pyroptosis-related genes in adipose tissue ( 106 ). Understanding the role of pyroptosis in chronic diseases such as DM allows for prevention and personalized treatment strategies.…”
Section: Exercise On Improving Diabetic Complications By Targeting Py...mentioning
confidence: 99%